MANAGEMENT OF IMPLEMENTATION OF INCLUSION EDUCATION AT SMP PGRI 01 BUMI AGUNG WAY KANAN - Al Ghifari, Dimas; Patimah, Hj. Siti (Riviera Publishing, 2023)
This research aims to determine inclusive education management in Way Kanan Regency. This research is a type of qualitative descriptive research. Data collection techniques include observation, interviews, and documentation. The research subjects were the school committee, school principals, teachers accompanying children with special needs, children with special needs, and parents of children with special needs. This research is a qualitative descriptive research. The data source in this research results from data collection carried out by observation, interviews, and documentation. To process the validity of the data using triangulation. Results of data analysis regarding the management of Inclusive Education at SMP PGRI 1 Bumi Agung Way Kanan. In essence, Education is the right of all children. Every child is born fitrah, including children with special needs. Inclusive Education aims to make teachers and students feel comfortable with diversity and view diversity as not a problem but a challenge for the school environment.